Tenofovir Versus Entecavir for Hepatocellular Carcinoma Prevention in an International Consortium of Chronic Hepatitis B. (11th February 2020) - Hsu, Yao-Chun; Wong, Grace Lai-Hung; Chen, Chien-Hung; Peng, Cheng-Yuan; Yeh, Ming-Lun; Cheung, Ka-Shing; Toyoda, Hidenori; Huang, Chung-Feng; Trinh, Huy; Xie, Qing; Enomoto, Masaru; Liu, Li; et al.
Abstract : INTRODUCTION: It is unclear whether entecavir (ETV) and tenofovir disoproxil fumarate (TDF) differ in their effectiveness for preventing hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB). METHODS: This retrospective cohort study analyzed an international consortium that encompassed 19 centers from 6 countries or regions composed of previously untreated CHB patients then treated with either ETV or TDF monotherapy. Those who developed HCC before antiviral treatment or within 1 year of therapy were excluded. The association between antiviral regimen and HCC risk was evaluated using competing-risk survival regression. We also applied propensity score matching (PSM) to 1:1 balance the 2 treatment cohorts. A total of 5, 537 patients were eligible (n = 4, 837 received ETV and n = 700 received TDF) and observed for HCC occurrence until December 23, 2018. Before PSM, the TDF cohort was significantly younger and had generally less advanced diseases. RESULTS: In the unadjusted analysis, TDF was associated with a lower risk of HCC (subdistribution hazard ratio [SHR], 0.45; 95% confidence interval [CI], 0.26–0.79; P = 0.005). The multivariable analysis, however, found that the association between TDF and HCC no longer existed (SHR, 0.81; 95% CI, 0.42–1.56; P = 0.52) after adjustment for age, sex, country, albumin, platelet, α-fetoprotein, cirrhosis, and diabetes mellitus. Furthermore, the PSM analysis (n = 1, 040) found no between-cohort differences in HCC incidences ( P = 0.51) and no association between regimens (TDF or ETV) and HCC risk in the multivariable-adjusted analysis (adjusted SHR, 0.89; 95% CI, 0.41–1.92; P = 0.77). DISCUSSION: TDF and ETV did not significantly differ in the prevention of HCC in patients with CHB.